2019
DOI: 10.1002/acr.23815
|View full text |Cite
|
Sign up to set email alerts
|

Tender Joint Count and Inflammatory Activity in Patients With Established Rheumatoid Arthritis: Results From a Longitudinal Study

Abstract: ObjectiveThe tender joint count (TJC) is included in composite disease activity scores (CDAS) (the Disease Activity Score in 28 joints, the Clinical Disease Activity Index, and the Simplified Disease Activity Index). The impact of having predominantly tender joints was explored by use of the Tender‐Swollen Joint Count Difference (TSJD), and ultrasound (US) provided a measure of joint inflammation. The current study aimed to explore the cross‐sectional and longitudinal associations between the TSJD and a spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 37 publications
5
34
0
2
Order By: Relevance
“…Examinations at patient level of the present cohort have shown patients with pain catastrophising to have higher levels of all the patient-reported outcomes including tender joint count but no differences in ultrasound scores,23 and patients with higher number of tender than swollen joints were found to have higher levels of composite scores but lower levels of ultrasound sum scores 33…”
Section: Discussionmentioning
confidence: 50%
“…Examinations at patient level of the present cohort have shown patients with pain catastrophising to have higher levels of all the patient-reported outcomes including tender joint count but no differences in ultrasound scores,23 and patients with higher number of tender than swollen joints were found to have higher levels of composite scores but lower levels of ultrasound sum scores 33…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, tenderness might reflect structural damage and fibromyalgia with central sensitization potentially influencing the composite disease activity score in some patients. (84,(194)(195)(196)(197). In a review by Navarro-Compan, all composite disease activity scores that included swollen joints were related to radiographic progression, as were the single components directly reflecting inflammation (such as SJC and ESR/CRP).…”
Section: Prediction Of Sustained Remission In Early Ramentioning
confidence: 99%
“…Moreover, many studies have reported that pain is a crucial and distressing symptom of RA (Jia & Jackson, 2016;Sturgeon et al, 2016). However, most of these studies have failed to show a strong relationship between pain in RA and objective measures of inflammation (Egsmose & Madsen, 2015;Hammer, Michelsen, Provan et al, 2018). In the past few years, more studies have discovered the influence of several pain appraisal variables, including cognitive beliefs, and behavioral and social responses, to explain the impact of RA on HRQoL (Morgan, 2013;Santos, Duarte, Ferreira, Pinto, Geenen & da Silva, 2018;Sturgeon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%